A comparative legal study of the dilution of registered trade marks in selected jurisdictions to further the development of the remedy in South African law - Van der Walt, Elizabeth Margaretha (Stellenbosch University, 2005)
Trade marks are among the most valuable commodities of the modern business world. Adequate protection for trade marks to prevent the misappropriation of their incredible marketing power is therefore important. The aim of this dissertation is to make recommendations regarding the further development of existing South African law regarding the protection of registered trade marks against dilution, particularly by the courts. Current statutory protection is examined and compared with trade-mark law in the United States and the European Union. Although the concept of dilution originated in Germany, most of its development took place in the United States, starting in 1927 with an article by Frank Schechter. Dilution occurs when the awareness that a specific mark signifies a single product from a single source changes to an unmistakable awareness that the same mark signifies various things from various sources. The primary theories as to how dilution occurs are blurring and tarnishment. Although the dilution concept is widely recognised, there is still a debate amongst legal scholars on whether trade marks deserve protection against dilution. The extent of protection that the law gives to trade marks largely depends on the socioeconomic functions that a trade mark is perceived to fulfil. The original source or origin function is protected by the traditional infringement provisions. The identification or distinguishing function, quality function and advertising function subsequently gained recognition. The advertising function is statutorily recognised in various jurisdictions, which prevents trade-mark dilution. Statutory recognition of dilution in the United States first occurred in State law from 1947 onwards. Protection is generally given to distinctive or strong trade marks where a similar mark is used on dissimilar goods in the absence of confusion in such a way that there is a likelihood that the reputation of the senior mark will be injured. The parameters of the concept were developed and refined mainly through case law. Federal protection against dilution was only introduced in 1995. The new Act, although widely welcomed, also brought some unpredictability and interpretation problems. The first statutory dilution protection for trade marks in Europe is found in the Uniform Benelux Trade Marks Act. In 1989 the European Union adopted the Trademark Directive, with the aim of harmonising the legal protection afforded to trade marks. Its "dilution" provisions were incorporated into the United Kingdom's Trade Marks Act of 1994. The sometimes conflicting interpretations of these provisions by the English courts and the Court of Justice of the European Communities are discussed. The South African Act shows a substantial degree of harmony with legislation in the United Kingdom and other European countries. Aspects of the wording of the dilution provisions are however open to interpretation by the courts. Until the end of 2003 there was only one major trade-mark dilution case decided by a South African court, namely SAR v Laugh It OjJPromotions, which is discussed in detail. The dissertation concludes with recommendations to aid South African courts in the future interpretation and application of the dilution provisions. Amendments to the legislation are also proposed to promote greater clarity.
Keywords: Brand name products; Comparative law; European Union countries; Intellectual property; South Africa; Trademarks; United States

L’œuvre audiovisuelle dans les États de l’Organisation africaine de la propriété intellectuelle (OAPI) - Ngombé, Laurier Yvon (Les Cahiers de propriété intellectuelle, 2005)
Keywords: Droit d'auteur; Intellectual property; Propriedade intelectual; Propriété intellectuelle